Postcard from Eugène Lemercier to his mother, Marguerite Lemercier, giving details about his second day of training - Lemercier, Eugène Emmanuel, 1886-1915; Lemercier, Marguerite, 1859-ca. 1930 (1915)
Comments about the welcome given by population on whom they are quartered and conditions in which he is serving : "moins pénible que les souffrances physiques et morales du front". Comments about physical exercise now perceived as a "holiday".
Addressed to "Madame Lemercier / 40 Rue Lauriston / Paris". No postmark.
There is an illustration in colour on the front of the postcard of 7 flying flags (of the allies), tied at the flagpole by a yellow ribbon, by "Stern graveur".
Keywords: Lemercier, Eugène Emmanuel, -- 1886-1915 -- Correspondence; World War, 1914-1918 -- France; World War, 1914-1918 -- France -- Correspondence; France -- History -- 1914-1940